2016
DOI: 10.1016/j.jcmg.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mammography and Screening for Coronary Artery Disease

Abstract: There is a strong quantitative association of BAC with CAC. BAC is superior to standard cardiovascular risk factors. BAC is equivalent to both the FRS and PCE for the identification of high-risk women and is additive when women with established CAD are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 23 publications
3
50
0
21
Order By: Relevance
“…При стандартном описании маммографии по шкале BI-RADS нормальная маммограмма с КМА имеет категорию 1 (отрицательная) или 2 (доброкачественная) [13], но чаще КМА не регистрируется вообще, как не имеющий отношение к диагностике рака молочной железы. Кальциноз артерий молочной железы Breast arteries calcification В ряде научных исследований для количественной оценки КМА применяется 12-балльная шкала, в которой учитывается число вовлеченных артерий, протяженность кальцинированных участков и их плотность [14,15]. Индекс КМА может иметь показатель от 0 до 12 для каждой молочной железы.…”
Section: патоморфология кальциноза маммарных артерийunclassified
“…При стандартном описании маммографии по шкале BI-RADS нормальная маммограмма с КМА имеет категорию 1 (отрицательная) или 2 (доброкачественная) [13], но чаще КМА не регистрируется вообще, как не имеющий отношение к диагностике рака молочной железы. Кальциноз артерий молочной железы Breast arteries calcification В ряде научных исследований для количественной оценки КМА применяется 12-балльная шкала, в которой учитывается число вовлеченных артерий, протяженность кальцинированных участков и их плотность [14,15]. Индекс КМА может иметь показатель от 0 до 12 для каждой молочной железы.…”
Section: патоморфология кальциноза маммарных артерийunclassified
“…More recently, a study by Margolies et al 4 provided the most detailed assessment of the association between BAC and CAC. The authors studied a convenience sample of 292 women referred for a mammogram who also underwent a clinically indicated nongated chest computed tomogram within a year of the mammogram.…”
Section: Breast Arterial Calcification Expanding the Reach Of Cardiovmentioning
confidence: 99%
“…If the patient does not already have a clear indication for a statin, then one could proceed to formal CAC testing. Margolies et al 4 reported a specificity and positive predictive value of BAC for CAC of 83 and 53, As with CAC screening, there is the theoretical concern that a diagnosis of BAC might have negative psychological consequences. Studies of adults who have undergone CAC testing have not substantiated such concerns.…”
Section: Breast Arterial Calcification Expanding the Reach Of Cardiovmentioning
confidence: 99%
“…In another recent study, Margolies et al investigated the relationship of BAC with CAC in 292 women without known CAD who had undergone noncontrast chest CT for various clinical indications at a single institution in New York . Although most other studies used Agatston scoring, Margolies et al assigned a CACS based on the extent of calcification in the 4 main coronary arteries.…”
Section: Summary Of Literature On the Association Of Bac With Coronarmentioning
confidence: 99%